Factores motivacionales que afectan en las ventas de los representantes financieros del Banco Interbank tienda 615, en el año 2016 - Santa María Mimbela, Laura (2017)
The present thesis was elaborated with the purpose of determining in what way the motivational factors affect in the sales of the financial representatives of the Bank Interbank store 615, in the year 2016. According to the research design we have that is the Descriptive - Correlational, because of the relationship between the two variables in the same sample. With regard to it we have the population made up of the 8 financial representatives of Bank Interbank 615 store in Trujillo; and non-probabilistic sampling and Pearson's correlation were used to determine the level of correlation of significance between the motivational factors and the sales volume. The results of the statistical application show that the motivational factors have a significant direct correlation with the sales volume, obtaining a Pearson correlation of 0.646. It is therefore concluded that motivational factors significantly affect the sales of the financial representatives of the Bank Interbank store 615.